2022
DOI: 10.1161/hypertensionaha.121.18754
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arterial Stiffness and Carotid Intima-Media Thickness Progression on the Risk of Dysglycemia, Insulin Resistance, and Dyslipidemia: a Temporal Causal Longitudinal Study

Abstract: Background: We investigated the temporal causal longitudinal associations of carotid-femoral pulse wave velocity (cfPWV), a measure of arterial stiffness, and carotid intima-media thickness (cIMT) progression with the risk of dysglycemia, insulin resistance, and dyslipidemia. Methods: We included 3862, 17.7-year-old, participants from the Avon Longitudinal Study of Parents and Children, followed up for 7 years. cfPWV, cIMT, and fasting plasma samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 37 publications
5
89
0
Order By: Relevance
“…A higher value of HOMAIR corresponds to a more severe IR. The study showed that a higher cfPWV at 17.7 years was associated with higher HOMA index at age 24.5 years, supporting the hypothesis according to which arterial stiffness in adolescence may be a causal risk factor for hyperinsulinemia and IR in young adulthood [ 9 ].…”
Section: Introductionsupporting
confidence: 64%
“…A higher value of HOMAIR corresponds to a more severe IR. The study showed that a higher cfPWV at 17.7 years was associated with higher HOMA index at age 24.5 years, supporting the hypothesis according to which arterial stiffness in adolescence may be a causal risk factor for hyperinsulinemia and IR in young adulthood [ 9 ].…”
Section: Introductionsupporting
confidence: 64%
“…Therefore, it is important to identify subclinical vascular damage in patients with MS and its components who should be taken into careful consideration for appropriate treatment. Increased arterial stiffness (AS) can be considered to be a good predictor of the development of subclinical cardiovascular dysfunction, so the assessment of AS can be useful in the identification of patients with increased cardiovascular risk [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive details of arterial stiffness assessments, haemodynamics, physics and mechanobiology have been published earlier [5,6,9,23]. This review summarizes recent epidemiological evidence on arterial stiffness usefulness in young population [20][21][22]24] and proposes future directions.…”
Section: Introductionmentioning
confidence: 99%